Material Hardships, Perceived Stress, and Health among Low-Wage Hospital Workers. Issue 1 (13th December 2021) - Woo, Jihee; Ballentine, Kess; Shook, Jeffrey; Engel, Rafael; Goodkind, Sara
Abstract: Many service, clerical, and technical hospital workers deemed essential during the pandemic have wages that do not reflect the essential nature of their work and do not earn enough income to cover basic expenses. Thus, many experience material hardships related to food, housing, and medical care. Previous studies have shown strong relationships between material hardships and health; however, they do not fully explain the role of stress as an intervening mechanism. This cross-sectional study analyzes an online survey with 257 lower-wage hospital workers to examine the relationships between hardships and health, and how perceived stress mediates these relationships. Path analysis revealed that financial and food hardships were related to mental health through perceived stress, while medical hardship was directly associated with physical health. These findings add to the evidence that workers' hardships either directly or indirectly contribute to negative mental and physical health outcomes through perceived stress. Future investigations should further examine relationships among material hardships, stress, and health, and advocacy efforts should focus on raising wages for essential hospital workers.